ANALYSIS OF INDONESIA SHARIA BANK'S HEALTH LEVEL ACCORDING TO FINANCIAL SERVICES AUTHORITY REGULATIONS - Kinanti, Sekar; Budiantoro, Harry; Gunawan, Andri; Lapae, Kanaya; Ningsih, Hestin Agus Tantri (Islamic Economics Program, Faculty of Islamic Economics and Business, 2024)
This study aims to determine and assess the Health Level of a bank using the Risk Profile, Good Corporate Governance, Earnings and Capital (RGEC) method of Bank Syariah Indonesia Quarter I 2021 - Quarter III 2022. This type of research is quantitative. The analysis used in this study uses Net Financing Performance (NPF), Financing to Deposit Ratio (FDR), Operating Expenses and Operating Income (BOPO) and Net Operating Margin (NOM). This study will compare and analyze the health level of banks at Bank Syariah Indonesia. Based on the research results, it can be concluded that Bank Syariah Indonesia for the NPF ratio shows an assessment of the bank's health level, namely